Taxonomy and phylogenetic studies revealed Parabambusicola yunnanensis sp. nov. (Parabambusicolaceae, Pleosporales) on bamboo from Yunnan, China - Han, Li-Su; Dai, Dong-Qin; Du, Tian-Ye; Wijayawardene, Nalin N.; Promputtha, Itthayakorn; Bhat, D. Jayarama; Gao, Yong (Phytotaxa, 2023)
A sample of bambusicolous ascomycete was collected from Dali, Yunnan Province, China. Multi-gene phylogenetic analyses based on a combined dataset of LSU, ITS, SSU, and tef1-α sequences showed that the new collection clusters within Parabambusicola s. str. but forms a separate branch (100% ML, 1.00 PP) basal to other Parabambusicola species. Additionally, morphological characteristics of the fungus resemble the members of Parabambusicola, with 8-spored asci, and fusiform to vermiform ascospores. The species was distinguished based on morphological and phylogenetic studies, thus, it is introduced here as a new species, viz., Parabambusicola yunnanensis. Morphological description, illustrations, phylogenetic tree, and a synoptic table of morphological characteristics for Parabambusicola are provided to show the taxonomic placement of the new species.